Graft Outcomes After Temporary Keratoprosthesis in Combined Penetrating Keratoplasty and Vitreoretinal Surgery. Issue 5 (19th May 2023) - Yu, Julia; Shalaby, Wesam Shamseldin; Shiuey, Eric J.; Rapuano, Christopher J.; Yonekawa, Yoshihiro; Hammersmith, Kristin M.; Nagra, Parveen K.; Syed, Zeba A.
Abstract : Purpose: Corneal pathology can obstruct the visualization required for surgical management of coexisting posterior segment diseases, and use of a temporary keratoprosthesis (TKP) permits combined penetrating keratoplasty (PK) and vitreoretinal surgery. We evaluated graft outcomes after TKP for combined PK and vitreoretinal surgery and analyzed risk factors for graft failure. Methods: We reviewed the electronic medical records for patients who underwent TKP for PK combined with vitreoretinal surgery at Wills Eye Hospital between May 2007 and April 2021. Overall, 28 variables were analyzed. The main outcome measure was corneal graft failure, defined as irreversible graft edema or opacification. Results: A total of 46 eyes of 46 patients underwent combined surgery and were included in the study. The mean age at surgery was 55.7 ± 18.6 years (range 19–86 years), and the mean follow-up was 31.8 ± 30.5 months (range 1.6–114.0 months). Multivariable analysis revealed 2 factors significantly associated with graft failure: history of trauma (hazard ratio = 5.38; 95% confidence interval, 1.53–18.91; P = 0.009) and intraocular silicone oil after transplant (hazard ratio = 5.67; confidence interval 1.66–19.44; P = 0.006). Corneal graft failure occurred in 60.9% of all cases over the course of follow-up, but the absence of both variables yielded a 33.3% failure rate. Conclusions: Although outcomes vary, previous ocular trauma and the presence of intraocular silicone oil are risk factors for failure that may facilitate patient selection and improve counseling about long-term graft potential after TKP for combined PK and vitreoretinal surgery.